Chronic outcomes of leadless vs transvenous single chamber ventricular pacemakers in high-risk subgroups. (3rd October 2022) - Boveda, S; Higuera, L; Longacre, C; Wolff, C; Wherry, K; Stromberg, K; Hinnenthal, J; Bockstedt, L; El-Chami, M
Abstract: Background: The Micra leadless pacemaker (LP-VVI) has been shown to have lower chronic complications and device-related reinterventions compared to transvenous ventricular pacemakers (TV-VVI) in a large, real-world population. This study compares the complication and reintervention rate in subgroups with comorbidities associated with higher risk of pacemaker complications and hypothesized to benefit from leadless pacing. Methods: The longitudinal Micra Coverage with Evidence Development (CED) Study compared the outcomes of Medicare patients receiving LP-VVI to those receiving a TV-VVI in the US. Patients in the Micra CED study were included in this study if they had a diagnosis of chronic kidney disease Stages 4–5 (CKD45), end-stage renal disease (ESRD), malignancy, diabetes, tricuspid valve disease (TVD), or chronic obstructive pulmonary disease (COPD) on any administrative claim in the 12 months prior to pacemaker implant. A pre-specified set of complications and system reinterventions were identified using the relevant diagnosis and procedure codes. Adjusted and unadjusted Fine-Gray competing risks models were used to compare reinterventions and complications between LP-VVI and TV-VVI patients within each subgroup. All results were adjusted for multiple comparisons using a Bonferroni correction. An ad-hoc comparison of a composite endpoint of select reinterventions (system replacement, removal, revision, and lead reinterventions) and device complications was also conducted. Results: The sample size of patients in each subgroup ranged from 2, 032 patients with ESRD to 11, 936 patients with diabetes. The percent of LP-VVI patients in each subgroup ranged from 44.0 in the TVD subgroup to 74.9 in the ESRD subgroup. Compared to patients implanted with a TV-VVI, patients with a LP-VVI with malignancy, diabetes, TVD, and COPD had significantly fewer complications (Table 1; Malignancy, HR 0.68, [0.48–0.95]; Diabetes, HR 0.69, [0.53–0.89]; TVD, HR 0.60 [0.44–0.82]; COPD, HR 0.73, [0.55–0.98]). LP-VVI patients with diabetes, TVD, and COPD also had lower rates of reintervention (Table; Diabetes, HR 0.58, [0.37–0.89]; TVD, HR 0.46 [0.28–0.76]; COPD, HR 0.51, [0.29–0.90]). LP-VVI patients with malignancy, diabetes, TVD, and COPD had lower rates of the combined endpoint of device complications and select reinterventions (Table; Malignancy, HR 0.52, [0.32–0.83]; Diabetes, HR 0.52, [0.35–0.77]; TVD, HR 0.44 [0.28–0.70]; COPD, HR 0.55, [0.34–0.89]). Conclusions: In a real-world study of US Medicare patients, the leadless pacemaker was associated with lower rates of chronic complications and reinterventions at 2 years compared with TV-VVI pacing in several high-risk subgroups. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic